Design and implementation of informatization for unified management of stroke rehabilitation in urban multi-level hospitals - Huang, Lihua; Jiang, Lan; Xu, Yiming; Ma, Yanhong (Frontiers in Neuroscience, 2023)
Background: With the aging of the population, the prevalence and incidence of stroke in China are increasing every year. China advocates the establishment of a three-level medical service system for stroke rehabilitation, but it lacks uniform information management among all levels of medical institutions. Objective: To achieve unified management of stroke patient rehabilitation in multilevel hospitals in the region through informatization construction. Methods: The need for informatization of three-level stroke rehabilitation management was analyzed. Then, network connections were established, and a common rehabilitation information management system (RIMS) was developed for all levels of hospitals to enable daily-stroke rehabilitation management, inter-hospitals referral, and remote video consultation. Finally, the impact on the functioning and satisfaction of stroke patients was investigated after implementing the three-level rehabilitation network. Results: One year after implementation, 338 two-way referrals and 56 remote consultations were completed using RIMS. The stroke RIMS improved the efficiency of doctors’ orders, reduced therapists’ time to write medical documents, and made referrals and remote consultations more convenient compared to the traditional model. The curative effect of stroke patients managed by RIMS is better than that of traditional management. The satisfaction with the rehabilitation services has increased among residents in the region. Conclusions: The three-level stroke rehabilitation informatization has enabled the unified management of stroke rehabilitation in multilevel hospitals in the region. The developed RIMS improves the efficiency of daily work, improves the function of stroke patients, and increases patient satisfaction.